Chemotherapeutic effects on larval stages of Schistosoma mansoni during infection and re-infection of mice Efeitos da quimioterapia nos estágios larvais do Schistosoma mansoni durante infecção e re-infecção de camundongos - Luciana M. Silva; Rejane M. C. Menezes; Sheilla Andrade de Oliveira; Zilton A. Andrade (Revista da Sociedade Brasileira de Medicina Tropical, 2003)
The sensitivity of the larval stages of Schistosoma mansoni to chemotherapy with praziquantel and oxamniquine was tested in mice during primary and secondary infections and after different intervals from cercarial exposure. Worm recovery by perfusion of the porto-mesenteric system, followed by counting and a morphometric study of the parasite, allowed the conclusion that the relative resistance of the larval stages of S. mansoni to schistosomicide drugs, demonstrated in primary infections, also persists when the host is already infected. This indicates that a therapeutic failure may result when an infected host is treated some time after being re-infected, because of the presence of migrating, drug-resistant, immature forms of the parasite. A susceptibilidade dos estágios larvais do Schistosoma mansoni aos esquistossomicidas praziquantel e oxamniquine foi testada em camundongos durante infecção primária ou secundária, e após diferentes intervalos de tempo após a exposição cercariana. A avaliação foi feita pela contagem dos vermes após recuperação destes por perfusão do sistema porto-mesentérico e pelo estudo morfométrico dos mesmos. O estudo revelou que a relativa resistência das formas larvais aos esquistossomicidas, já demonstrada em infecção primária, persiste no caso de hospedeiros já infectados. Este fato indica que uma falha terapêutica pode resultar quando o tratamento é feito em hospedeiros re-infectados recentemente, em virtude dos mesmos apresentarem formas migrantes e imaturas do parasita, as quais são particularmente resistentes aos esquistossomicidas.